2012
DOI: 10.1186/1472-6963-12-110
|View full text |Cite
|
Sign up to set email alerts
|

“Completely out-at-sea” with “two-gender medicine”: A qualitative analysis of physician-side barriers to providing healthcare for transgender patients

Abstract: BackgroundMembers of the transgender community have identified healthcare access barriers, yet a corresponding inquiry into healthcare provider perspectives has lagged. Our aim was to examine physician perceptions of barriers to healthcare provision for transgender patients.MethodsThis was a qualitative study with physician participants from Ontario, Canada. Semi-structured interviews were used to capture a progression of ideas related to barriers faced by physicians when caring for trans patients. Qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
198
0
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(225 citation statements)
references
References 25 publications
7
198
0
20
Order By: Relevance
“…Survey items inquiring about barriers to providing transgender-related care for youth were informed by a qualitative study focused on providers of transgender adults and the literature [8,9]. Clinical exposure to transgender youth was explored with items asking about the number of transgender patients for whom practitioners had provided care since completing training and whether a respondent had ever worked in a transgender clinic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey items inquiring about barriers to providing transgender-related care for youth were informed by a qualitative study focused on providers of transgender adults and the literature [8,9]. Clinical exposure to transgender youth was explored with items asking about the number of transgender patients for whom practitioners had provided care since completing training and whether a respondent had ever worked in a transgender clinic.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these changes, there have been no empirical studies assessing providers' comfort with and barriers to providing psychologic and/or medical care for transgender youth. A qualitative study found that perceived physician barriers to providing care for transgender adults included difficulty accessing psychosocial services for their patients, deficits in transgender-specific medical knowledge, and personal ethical dilemmas with transgender-related medical care; however, there are no comparable studies on transgender youth [8]. As adolescent medicine and pediatric endocrine providers are the medical specialists most represented in multidisciplinary gender centers across the United States [3], this study aims to explore these providers' clinical experiences, confidence, and comfort with and barriers to providing care for transgender youth.…”
mentioning
confidence: 99%
“…Our search did not produce any trans-positive behaviorchange interventions designed for HCPs. We found only two qualitative studies that explore physicianlevel barriers to delivering care to trans patients (Poteat, German, & Kerrigan, 2013;Snelgrove et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Professional guidelines for routine cervical cancer and STI screenings in this population are identical to those recommended for cisgender women. 21 Many FTM patients face barriers to receiving needed services due to a combination of factors, including stigma and discrimination, 22,23 lack of insurance and access to genderaffirmative health care, 24,25 patient and health care provider misperceptions pertaining to HPV and cervical cancer risk (Table 2), and apprehension about undergoing intrusive procedures such as pelvic examinations, 10 leading to decreased rates of cervical cancer screening compared to cisgender women. 26 In addition, due partially to the atrophying effect of testosterone on the cervical epithelium, cervical cytology specimens are approximately ten times as likely to be unsatisfactory among patients on the FTM spectrum as among cisgender women.…”
Section: Overview Of Key Clinical Concernsmentioning
confidence: 99%